Vitamin D deficiency: A review of the relationship between vitamin Deficiencies somedisease as Obesity, Diabetes and Cardiovascular in Al-Muthanna Province - Iraq - Aziz, Hanaa Ali; Azeez, Dhay Ali (International Journal of Psychosocial Rehabilitation, 2020)
Vitamin D deficiency is pandemic, and has been implicated in a wide variety of disease such obesity, diabetes and cardiovascular. Recent studies have found a relationship between vitamin D deficiency and an increase in the weight of people, it showed the presence of an enzyme responsible for the formation of vitamin D and the efficacy of metabolism , The lower action of this enzyme leads to a lack of vitamins and hence the low level of metabolic activity in people.Vitamin D deficiency predisposes individuals to type 1 and type 2 diabetes, and receptors for its activated form 1α,25-dihydroxyvitamin D3 have been identified in both beta cells and immune cells. The researchers shown role in the development of type 2 diabetes through impair insulin synthesis and secretion in humans andanimal models. Also , epidemiological studies suggest a link between vitamin D deficiency in early life and the later onset of type 1 diabetes. Also, several studies have reported that vitamin D deficiency is associated with increased risk of cardiovascular disease, including hypertension, heart failure and ischemic heart disease.